PENGARUH KUALITAS LAYANAN DAN HARGA TERHADAP LOYALITAS PELANGGAN BOTOL MINUM HERBALIFE PADA ONLINE SHOP - Nazilatul Barokah; Nuridin (Jurnal Ekonomi dan Industri, 2020)
The purpose of this study was to determine the effect of service quality and price on customer loyalty in herbalife drinking bottles at Pondok Gede Barat. The research method uses descriptive analysis of linear regression both partially and multiplely. The findings suggest that service quality can encourage increased customer loyalty, this can be seen from the reliability of employees in handling the needs of customer orders by paying serious attention, sending orders quickly and guaranteeing a sense of security and maintaining a good relationship with customers. Prices encourage increased customer loyalty, this is because the prices offered can be affordable that are tailored to the ability of customers with quality products that are in accordance with extraordinary prices and benefits.